Aktivitas Antioksidan Daun Sirsak (Annona muricate L.): A Systematic Review - Rahayu, Rinoa Sahda; Wulandari, Cyntia (State University of Gorontalo, 2025)
Antioxidants are compounds that can ward off free radicals that can affect health. This study aims to identify antioxidant compounds in soursop leaves through a literature review writing method with reference to PRISMA. Which was conducted between 12 and 14 December 2024 online through Dimension with the keywords